Risk Control Platform of Safety Production Based on Digital Twin - ZHANG Bo; ZHAO Songpeng (Renmin Zhujiang)
The construction of “six mechanisms” for risk control should be steadily promoted,including search,research and judgment,early warning,prevention,disposal,and responsibility of safety production risks in water conservancy,and the safety management of water conservancy projects should be improved. Therefore,this paper studies the characteristics and rules of safety production in operation management units of hydraulic engineering.Additionally,a safety production risk management and control platform framework based on digital twin is built to realize intelligent supervision of safety production risks.Taking the Baise water conservancy project as an example,this paper establishes a safe production risk control platform for this project.By achieving the existence of two safety production risk control scenarios of hydraulic engineering based on digital twin and operation,the feasibility of safety production risk control platforms based on digital twin is demonstrated.Meanwhile,a new idea is proposed for subsequent research on safety production risks,which is of certain guiding significance.